On the application of Newton's and Chord methods to bifurcation problems - M. B. M. Elgindi (International Journal of Mathematics and Mathematical Sciences, 1994)
This paper is concerned with the applications of Newton's and chord methods in the computations of the bifurcation solutions in a neighborhood of a simple bifurcation point for prescribed values of the bifurcation parameter.